Development of a Numeracy Test Instrument for Kuningan Cultural Tourism Based on Quizizz - Debia Nuriza; Imeldrif Tri Lestari; Lilis Fauziah; Niniek Rachmatu Adiyah; Nurnajib Al Fiqri; Rifky Tegar Nugraha; Tiara Dwi Mahardhika; Sumarni Sumarni (Universitas Negeri Surabaya, 2025)
This study aims to develop a numeracy test instrument based on the context of Kuningan cultural tourism using the Quizizz platform. This valid, reliable, and practical tool is used in the numeracy assessment of the Independent Curriculum (Curriculum Merdeka). This research is developmental research using the Plomp model, which includes preliminary research, design, and evaluation. The trial subjects involved 30 junior high school students in Kuningan Regency. Content validation was conducted by three experts in mathematics education, assessment, and local culture, and analyzed using the Aiken's V coefficient. Empirical testing included analysis of item validity, reliability, discrimination power, and difficulty index using classical test theory. The results showed that the Aiken's V value ranged from 0.83 to 0.94, with an average of 0.89, indicating high content validity. The instrument's reliability value of α = 0.79 is in the high category. Most of the test items had good discrimination power (0.40 ≤ D < 0.70) and a moderate difficulty index (0.30 ≤ p ≤ 0.80). These findings indicate that the developed instrument is suitable for use as a contextual numeracy assessment tool. Integrating Kuningan's cultural context, such as the Linggarjati Museum and Cibulan Pond, with the Quizizz platform has been shown to increase student engagement and provide a meaningful and enjoyable digital assessment. This research contributes to strengthening local culture-based numeracy literacy and supports the implementation of the Pancasila Student Profile through technology-based assessment. Keywords: ,, local culture, Quizizz,